Kriteria Pengambilan Keputusan Majemuk Pada Pemilihan Supplier Bahan Baku Kulit Sepatu - Putra, Fibi Eko; Iklimaturriza, Madania; Madiyani, Ani (DPPM UNIVERSITAS PELITA BANGSA, 2021)
Supplier selection is one of the important things in purchasing activities for a company. The selection of suppliers must be done carefully because the wrong choice of suppliers will cause the production process and operations of the company to be disrupted. One technique that can be used for supplier selection is the AHP (Analytical Hierarchy Process) method. The research was conducted at PT RZ, a shoe company that will work with shoe leather suppliers. This study aims to determine the best supplier preferences by criteria and sub -criteria. In the end, the rating is determined from the criteria for the relative importance of supplier selection: priority I is quality (0.450), priority II is price (0.265), priority III is service (0.127), and the next priority is delivery and quantity with equal priority (0.79). In the end, the rating is determined from the criteria for the relative importance of supplier selection: the first priority is Supplier X (0.500), the second priority is Supplier Z (0.312), and the next priority is Supplier Y (0.188). Related suppliers, the company can select Supplier X as the supplier of leather raw materials with the highest final value. With the selection of these suppliers, we hope to improve the performance of supply chain relationships between companies and suppliers in a better direction in the future.